Effects of oscillatory pressure mode on the sintering behavior of Al2O3w–ZrO2 composite in hot oscillatory pressing. Issue 12 (29th August 2022) - He, Hongtian; Shao, Gang; Zhao, Rui; Liang, Yi; Wang, Hailong; Fan, Bingbing; Lu, Hongxia; Xu, Hongliang; Zhang, Rui; An, Linan
Abstract: Hot oscillatory pressing (HOP) has been shown to be a more effective technology for sintering various material systems than hot pressing sintering due to the use of oscillatory pressure. However, the effect of oscillatory pressure parameters on the sintering behavior is not clear. In this paper, the effect of pressure amplitude, frequency, and mean pressure of oscillatory pressure on the sintering behavior was studied by using sapphire whisker reinforced zirconia ceramic composite as a model material. The obtained results were discussed by considering grain boundary sliding as a viscoelastic process. The current work would provide scientific guidance for determining optimized HOP parameters.